The institutional design of international double taxation avoidance; Das Design der internationalen Institutionen zur Vermeidung von Doppelbesteuerung - Thomas Rixen (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2008)
This article analyzes the institutional design of international double tax avoidance. The basic argument is that double tax avoidance exhibits the strategic structure of a coordination game with a distributive conflict. The distribution of tax revenues depends on the asymmetry of investment flows between treaty partners. Since investment flows are defined dyadically, bilateral bargaining can best accommodate countries' concern for the distribution of tax revenues and other economic benefits connected to the tax base. Moreover, because there are no serious externality problems with bilateral agreement, this solution is also viable. At the same time, there is a need for a multilateral organization to disseminate information and shared practices in the form of a model convention that provides a focal point for bilateral negotiations. The strategic structure of a coordination game can also explain why the institutions of double tax avoidance do not have to be equipped with third-party enforcement capabilities. Instead, the Mutual Agreement Procedure (MAP) is interpreted as a device to deal with the fact that double tax agreements (DTAs) are incomplete contracts. – – Dieser Artikel analysiert die institutionelle Form der internationalen Kooperation zur Vermeidung von Doppelbesteuerung. Es wird argumentiert, dass das Doppelbesteuerungsproblem als ein Koordinationsspiel mit Verteilungskonflikt verstanden werden kann. Die Verteilung der Steuereinnahmen hängt von der Asymmetrie der Investitionsflüsse zwischen den vertragsschließenden Staaten ab. Da diese Investitionspositionen notwendigerweise paarweise variieren, können die Verteilungsinteressen der Staaten am besten in bilateralen Verhandlungen aufeinander abgestimmt werden. Weil es außerdem bei bilateralen Doppelbesteuerungsabkommen keine Externalitäten gibt, sind solche Verträge auch durchsetzbar. Trotzdem gibt es Bedarf für eine multilaterale Organisation, die Informationen und gemeinsame Praktiken in Form eines Modellabkommens verbreitet. Das Modellabkommen dient als Fokalpunkt für die bilateralen Verhandlungen. Die strategische Struktur als Koordinationsspiel kann außerdem erklären, warum die Institutionen der Doppelbesteuerungsvermeidung nicht mit Durchsetzungskapazitäten ausgestattet sind. Das sogenannte Verständigungsverfahren zur Beilegung von Vertragsstreitigkeiten dient vielmehr als Instrument zur Bearbeitung des Problems unvollständiger Verträge.
Keywords: 300; Doppelbesteuerung; Neue Institutionenökonomik; Spieltheorie; Steuerwettbewerb; Verhandlungen; Theorie